Odpowiedź :
Odpowiedź:
[tex]\huge\boxed{kot-5kg}\\\boxed{pies-35kg}\\\boxed{Adam-65kg}[/tex]
Szczegółowe wyjaśnienie:
[tex]k[/tex] - masa kota (kg)
[tex]7k[/tex] - masa psa (kg)
[tex]7k+30[/tex] - masa Adama (kg)
[tex]105[/tex] - masa wszystkich (kg)
RÓWNANIE:
[tex]k+7k+7k+30=105\\\\15k+30=105\qquad|-30\\\\15k=75\qquad|:15\\\\\boxed{k=5}\\\\7k=7\cdot5\\\\\boxed{7k=35}\\\\7k+30=35+30\\\\\boxed{7k+30=65}[/tex]
Odpowiedź:
(P) Pies - 35 kg
(K) Kot - 5 kg
(A) Adam - 65 kg
Szczegółowe wyjaśnienie:
P + K + A = 105 kg
P = 7 * K
P + 30 kg = A
[tex]\frac{1}{7}[/tex] x + x * 2 + 30 kg = 105 kg ---> x to Pies
[tex]\frac{1}{7}[/tex]x + 2x + 30 kg = 105 kg | * 7
([tex]\frac{1}{7}[/tex]x + 2x + 30 kg) * 7 = 105 kg * 7
x + 14x + 210 kg = 735 kg
15x + 210 kg = 735 kg
15x = 735 kg - 210 kg
15x = 525 kg | : 15
x = 35 kg
35 kg : 7 = 5 kg
35 kg + 30 kg = 65 kg
SPRAWDZENIE:
65 kg + 35 kg + 5 kg = 105 kg